(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Hepatic encephalopathy is a neuropsychiatric complication that occurs in patients with advanced liver disease, resulting in a variety of neurological and psychiatric symptoms. Effective treatment is of paramount importance due to the morbidity associated with this condition. Objective: This study aims to review current therapeutic approaches for hepatic encephalopathy, highlighting common treatment strategies and future prospects for therapeutic intervention. Methodology: The review was conducted by searching scientific databases, including relevant clinical trials, to identify therapeutic strategies used in hepatic encephalopathy. Results: Common therapeutic approaches for hepatic encephalopathy include dietary protein restriction, the use of Lactulose for ammonia excretion, and the administration of antibiotics such as rifaximin to reduce ammonia-producing intestinal flora. Various research efforts are underway to discover future pharmacological therapies. Conclusion: The therapeutic approach to hepatic encephalopathy is multifaceted, aiming to alleviate acute symptoms and prevent recurrences. A multidisciplinary strategy is essential for the effective management of this complex condition, and ongoing research is exploring new therapies that may improve the prognosis and quality of life for affected patients. Understanding the pathophysiology of hepatic encephalopathy is evolving, offering hope for more effective treatments in the future.